Strategi Pedagogis Dosen Pendidikan Agama Islam dalam Menginternalisasi Nilai Moderasi Beragama di Perguruan Tinggi - Irfan Anshori (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2026)
This study aims to empirically examine the pedagogical strategies of Islamic Religious Education lecturers in the process of internalizing the value of religious moderation in higher education. This study was carried out at Serang Raya University using a descriptive qualitative approach. Data was collected through in-depth interviews with PAI lecturers, observation of the learning process in the classroom, and analysis of relevant learning documents. The results of the study show that the internalization of the value of religious moderation is not carried out explicitly through the delivery of normative material alone, but through pedagogical strategies that are dialogical, reflective, and contextual. PAI lecturers facilitate open discussion spaces, encourage students to think critically about contemporary religious issues, and relate teaching materials to students' social realities. This strategy has been proven to contribute to forming a more moderate, tolerant, and inclusive attitude of students. This research has important significance because it enriches the study of religious moderation in Islamic Religious Education from the perspective of pedagogy and learning praxis. The findings of this study are expected to be a reference for lecturers and managers of higher education in developing PAI learning that is oriented towards strengthening religious moderation in the university environment.